431 DIABETES AS AN INDEPENDENT RISK FACTOR FOR ANEMIA IN CHRONIC KIDNEY DISEASE. (1st January 2005) - Ghanekar, H.; Poole, T.; Toto, R.
Abstract : The aim of our study was to determine whether diabetics (DM) are more likely to be anemic at a similar stage of CKD as compared to nondiabetics (NDM), and if such a difference exists, the probable factors contributing to it. We studied 82 DM and 59 NDM consecutive patients with stage III and IV CKD seen in the Parkland Hospital's CKD clinic between February 2003 through April 2004. There were no differences in age, gender or ethnicity between DM and NDM patients. Hemoglobin concentration (Hb) and RBC indices were measured on all patients at the initial visit. Serum Fe, TIBC, ferritin, and stool guaiac were performed on all patients with a Hb of < 11 g/dL at the initial visit. None of the patients were taking iron supplements or erythropoietin. CKD stages were based on MDRD estimated GFR. Anemia was defined as Hb < 12 g/dl in males and < 11 g/dL in females. The table illustrates initial Hb (mean ± SD) and fraction of DM and NDM patients with anemia. A higher percentage of DM, 84% (16/19), as compared to NDM, 60% (6/10), had transferrin saturation less than 20%. Presence of absolute iron deficiency (serum ferritin < 100 ng/mL) was higher in DM as compared to NDM (58% vs 40%). The mean RBC indices were normocytic normochromic in both DM and NDM. Stool guaiac was negative in all patients except one NDM patient. Therefore, gastrointestinal blood loss cannot explain the abnormal iron indices. We conclude that DM patients have a higher prevalence of anemia and a lower Hb than NDM patients at a similar stage of CKD. These data suggest that both dietary iron absorption and utilization are impaired to a greater extent in DM with CKD as compared to NDM with CKD.